Effectiveness of Rhizosphere Azotobacter Bacteria in Promoting Rice Growth and Yield in a Greenhouse - Purwaningsih, S; Mulyani, N; Nugroho, A A; Suriani, N L (KnE Life Sciences, 2022)
Azotobacter is a nitrogen-fixing bacteria. The growth and yield of rice (Oryza sativa L) in a greenhouse were studied to examine physiological characterization and efficacy of Azotobacter isolated from the rhizosphere and soil. The goal was to isolate Azotobacter that could be used as a biological fertilizer. There were 21 Azotobacter isolated, with 17 capable of nitrogen-fixing activity, 16 capable of protease activity, six capable of IAA activity, and 13 capable of phosphate dissolution. Each treatment was carried out three times in the experiment, which was completely randomized. At 105 days, the seedlings were harvested. The height of the plants, the number of leaves, the dry weight of the straw and grain, and the number of panicles and seeds were all evaluated. The results showed that rice yields were higher when 1 KZ was isolated from the turi plant (Sesbania grandiflora) and 15 KZ was isolated from the akasia plant (Acasia mangium). Keywords: Azotobacter, Rice Growth, Plant Growth Promoting Rhizobacteria